ANALISIS PENGARUH CASH FLOW, FIRM SIZE, FINANCIAL LEVERAGE, DAN CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN - Titi Indati Ahmariah; Nur Cahyonowati (Diponegoro Journal of Accounting, 2026)
The influence of various factors on financial performance is a crucial issue for companies as well as their stakeholders. This is because optimal financial performance not only ensures the continuity of operational activities but also enhances investor confidence, strengthens market position, and serves as a basis for making strategic decisions in the future. This study aims to examine the relationship between cash flow, firm size, leverage, and corporate governance mechanisms—represented by board size, audit committee meeting frequency, and board duality—on financial performance, as proxied by Return on Assets (ROA). The population of this study consists of all manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was determined using purposive sampling, resulting in 274 observations from 70 companies. The data used were secondary data obtained from audited financial statements and annual reports. The findings indicate that cash flow has a positive and significant effect on ROA, firm size has a positive and significant effect on ROA, financial leverage has a negative and significant effect on ROA, and board size has a negative and significant effect on ROA. Meanwhile, audit committee meeting frequency and board duality have positive but insignificant effects on ROA.